Exploring the chemistry of backbone amino(chloro)phosphanyl-substituted imidazole-2-thiones. Issue 31 (31st July 2017) - Koner, Abhishek; Serin, Spencer C.; Schnakenburg, Gregor; Patrick, Brian O.; Gates, Derek P.; Streubel, Rainer
Abstract : Backbone amino(chloro)phosphanyl-substituted imidazole-2-thiones were synthesized and their potential as starting material for backbone phosphaalkenyl substituted imidazole-2-thiones studied. Abstract : Backbone (R′2 N)2 P-substituted imidazole-2-thiones2a–c [(R′2 N)2 P-IMS R, R ; IMS R, R = 1, 3-dialkylimidazole-2-thione-4-yl, a : R = i Pr, R′ = Et;b : R = Mes, R′ = Et, c : R = Me, R′ = i Pr] were treated with PCl3 to synthesize R′2 N(Cl)P-substituted imidazole-2-thiones3a–c [R′2 N(Cl)P-IMS R, R ]. The P -chloro compounds3a, b were used to explore the chemistry further, i.e. nucleophilic substitution at phosphorus using Ph2 CHLi or fluorenyl lithium afforded compounds4a–c [R′2 N(R′′)P-IMS R, R ;a : R = i Pr, R′ = Et, R′′ = PH2 CH;b : R = Mes, R′ = Et, R′′ = Fluc : R = i Pr, R′ = Et, R′′ = Flu]. Compound4c was used to access the P -borane adduct5 [R′2 N(R′′)(BH3 )P-IMS R, R ; R = i Pr, R′ = Et, R′′ = Flu] and phosphinoyl-substituted imidazolium hydrogensulfate6 [[R′2 N(R′′)(O)P-IMH R, R ]HSO4 ; IMH R, R = 1, 3-dialkylimidazolium-4-yl, R = i Pr, R′ = Et, R′′ = Flu]. Compounds4a, b were transformed into the P -Cl compounds7a, b [R′′(Cl)P-IMS R, R ;a : R = i Pr, R′′ = Ph2 CH;b : R = Mes, R′′ = Flu] which represent potential starting materials for backbone phosphaalkenyl substituted imidazole-2-thiones. Compound7a yielded the NHC-stabilized phosphenium salt8 [[R′′(IMe4 )P-IMS R, R ]Cl; R = i Pr, R′ = Et, R′′ = Ph2 CH, IMe4 = 1, 3, 4, 5-tetramethylimidazole-2-ylidene] in reaction with 1, 3, 4, 5-tetramethylimidazole-2-ylidene (IMe4 ). Attempts to deprotonate7a, b using n BuLi revealed that nucleophilic substitution of P –Cl to give the P - n Bu product occurred preferentially, and dehydrochlorination to the phosphaalkene was not observed.